Teaching the Art of Poetry : the Moves. - Wormser, Baron (Taylor & Francis Ltd., 1999)
Written w/ classroom teachers in mind, this bk is a guide to the art of poetry & a focused approach to how to teach poetry. It focuses on two main issues: how poetry is defined, perceived, & taught, & how it can become more integrated into students' live.